Implementasi Nilai-Nilai Profetik pada Kisah Nabi Musa dalam Al-Qur’an - Ach. Khatib ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2019)
The research describes implementations of prophetic values of Prophet Musa's (Moses) story in the Qur'an verse. Musa's life story, ranging from the beginning, childhood, to the end of his endeavor, abounds with meaning and values that can be adopted as human life principles. The article used a qualitative method with a phenomenological approach to reveal the prophetic values of Prophet Musa. In disclosing the prophetic values of Prophet Musa, the researcher adopted Kuntowijoyo's and Muhammad Ali Ash-Shobuni's theories. The research showed that the prophetic values of Prophet Musa carry profound messages. The values that can be learned range from, to name a few, being reliable, intelligent, people's savior, altruistic, fearless, consistent, spiritually brilliant, unwavering, healthy mentally and physically, open to criticism and suggestion, sympathetic, professional, transcendent, to persistent.